(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Drinking water or potable water also known as improved drinking water is said to be any water that is free from physical, chemical, biological or radiological form of contamination. Water samples were collected from 5 rivers in Omuchi Aluu, Choba, Chokocho, Oyigbo, and Aleto communities, in Rivers State, Nigeria, used for activities such as washing, bathing, fishing, and dredging by community indigenes. Water samples were collected from various sampling stations and, transported to the laboratory, African Biosciences, Ibadan for analysis to characterize and identify the protozoan parasites using molecular techniques. This study aimed at characterizing the genotype of protozoan parasites of water from selected rivers in River State, Nigeria, using molecular methods to check for portability and purity of water. DNA Primers of five protozoan parasites, Giardia species, Entamoeba species, Cryptosporidium species, Cyclospora species, and Toxoplasma species were used to analyze and detect the presence of the genes of these protozoans. The study showed the presence of Giardia duodenalis and Cryptosporidium parvuum, and the absence of Entamoeba histolytica, Cyclospora cayetanensis, and Toxoplasma gondii from the water samples collected from Omuchi Aluu, Choba, Chokocho, Oyigbo, and Aleto rivers. It was concluded that water samples collected from rivers contaminated with parasites, is unsuitable for drinking, hence community locals should be sensitized to embark on good water sanitary and hygiene (WASH) practices, for a healthy life and sustainable environment.